Internal Auditing and Quality of Banking Accounting Information in Private Banks - Twair, Najat Jaber; Yaseen, Jasim Mohammed; Jasim, Abdullah Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The increasing complexity of banking operations has intensified the need for reliable, high-quality accounting information to support sound financial decisions. Specific Background: Internal auditing has evolved into a strategic assurance and advisory function that enhances organisational control and strengthens financial reporting practices in the banking sector. Knowledge Gap: However, the extent to which internal auditing, through its operational efficiency, communication practices, and audit outputs, contributes to improving the quality of banking accounting information in private banks remains insufficiently examined, particularly within the context of Najaf Governorate. Aims: This study investigates the impact of internal auditing and its dimensions on the quality of banking accounting information, using data from 70 administrative leaders across five major private banks. Results: Structural equation modelling revealed a strong and significant positive effect of internal auditing on information quality (β = 0.621), with reliance on audit outputs showing the greatest influence (β = 0.411). Novelty: The study demonstrates empirically that managerial utilisation of audit outputs mediates the improvement of both fundamental and enhancing characteristics of accounting information. Implications: These findings highlight the need to strengthen audit–management communication and to institutionalise audit recommendations as strategic tools for enhancing financial reporting integrity in private banks.Highlight : The study emphasizes the strong influence of internal auditing on improving the quality and reliability of banking accounting information. Reliance on internal audit outputs appears as the most impactful dimension in enhancing information usefulness for decision-making. The findings highlight areas that still require improvement, particularly communication and cooperation between auditors and management Keywords : Internal Auditing, Banking Accounting Information Quality, Private Banks, Audit Outputs, Najaf Governorate